Digital Surveillance to Combat Covid-19 Crisis: How to Strictly in Line With Human Rights? - Pranoto,; Firmandiaz, Viddy; Priskarini, Intan Audia (International Journal of Psychosocial Rehabilitation, 2020)
Surveillance is one of the most effective ways for the government to maintain and control the societies to achieve a common good for its citizens, especially in the time of crisis. Digital Surveillance is an essential way during the combat against COVID-19 pandemic that leads the government to maintain the spread of the virus by using personal data to locate and track risk individual’. However, the government must be facing the crisis responsibly and do not disregard any human rights at any cost. This study analyzes how to execute digital surveillance in line with human rights. Digital surveillance must be executed transparently about the time of the surveillance, the government must protect the collected data by ensuring the security of any personal data collected, and any uses of digital surveillance must be for emergency purposes only. Human Rights still apply under any circumstances, including state of emergency, to prevent the state’s abuse of power.